Magnetic solid phase extraction using Fe3O4@SiO2@C8 nanoparticles performed in a narrow-bore tube followed by dispersive liquid–liquid microextraction for extraction and preconcentration of nine pesticides. (26th March 2018) - Farajzadeh, Mir Ali; Yadeghari, Adeleh; Khoshmaram, Leila
Abstract : In the present work, a new magnetic solid phase extraction method performed in a narrow-bore tube using synthesized Fe3 O4 @SiO2 @C8 magnetic nanoparticles has been developed. Abstract : In the present work, a new magnetic solid phase extraction method performed in a narrow-bore tube using synthesized Fe3 O4 @SiO2 @C8 magnetic nanoparticles has been developed. The method was designed to extract and preconcentrate trace amounts of some pesticides in fruit and vegetable samples. To obtain low limits of detection, a dispersive liquid–liquid microextraction method was performed after magnetic solid phase extraction. In the practical procedure, small amounts of the sorbent were added and moved down through the aqueous solution of the analytes placed in the tube under force of gravity instead of passing the solution from a cartridge, as performed in traditional solid phase extraction. Subsequently, the sorbent which collected at the bottom of the tube was transferred to the top of the solution using an external magnet and was released to move down through the solution. This step was repeated four times in order to increase the extraction efficiency. Then, the adsorbed analytes were desorbed using methanol. The extract was subjected to dispersive liquid–liquid microextraction. Under the optimum extraction conditions, the method showed wide linear ranges with low limits of detection (0.03 to 0.17 μg kg −1 ). Enrichment factors and extraction recoveries were in the ranges of 2133 to 2733 and 64% to 82%, respectively. The relative standard deviations for 5, 20, and 100 μg L −1 of each analyte were equal to or less than 8% for intra-day ( n = 6) and inter-day ( n = 4) precisions.